Radical (chemo)radiotherapy in oropharyngeal squamous cell carcinoma: Comparison of TNM 7th and 8th staging systems. (April 2020) - De Felice, F.; Bird, T.; Michaelidou, A.; Thavaraj, S.; Odell, E.; Sandison, A.; Hall, G.; Morgan, P.; Lyons, A.; Cascarini, L.; Fry, A.; Oakley, R.; et al.
Highlights: The 8th TNM edition has received growing attention in oropharyngeal cancer (OPC). We analyzed survival outcomes compared with 7th and 8th editions in OPC patients after radical chemoradiotherapy (CRT). Our data showed a better OS stratification in OPC after definitive CRT. Abstract: Purpose: To evaluate whether the 8th staging system is a better discriminator of overall survival (OS) than the 7th edition for oropharyngeal cancer patients after definitive (chemo)radiotherapy (CRT). Material and methods: Data from oropharyngeal cancer patients treated with CRT with curative intent between 2010 and 2016 at Guy's and St Thomas' Hospitals were reviewed. Human papillomavirus (HPV) status was ascertained in all cases. Patients were staged using the 7th edition and the 8th edition TNM staging system. Demographics, tumor characteristics and treatment response data were included in univariate and multivariate analysis for OS. OS and disease-free survival (DFS) were estimated using the Kaplan-Meier method. In addition, a multivariate survival Cox regression analysis of several clinical variables was performed. Results: A total of 273 patients were included. The median follow-up was 4.7 years. Overall 63 patients died. In multivariate analysis, HPV status, complete response at 3 months and ≤21 units/week alcohol were prognostic for OS. For the entire cohort, the 5-year OS and DFS rates were 78.1% (95% confidence interval CI 0.719–0.831) and 73.9% (95% CI 0.677–0.792), respectively. Better stratification of OS and DFS was recorded by 8th edition for the entire cohort. In HPV-positive cases, risk stratification based on tobacco smoking and nodal stage resulted in statistically higher discrimination in OS rates (5-year OS 90.7% in low risk patients and 84.6% in intermediate risk, p  = 0.05) and DFS rates (5-year DFS 91.5% in low risk and 76.1% in intermediate risk, p  = 0.001). Conclusion: The 8th edition TNM staging system provides better OS stratification in oropharyngeal cancer after definitive CRT compared with the 7th edition. Other clinical variables, such as complete response at 3 months, alcohol and tobacco smoking, should also be considered in future classifications as they provide additional risk stratification information in both HPV-positive and HPV-negative disease.